The Effect of Exercise Method and Body Mass Index on Time Exhaustion, Lung’s Vital Capacity and VO2Max (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The aims of this study are (1) to analyze the differences in the effect of the Exercise Method on Time Exhaustion, Lung’s Vital Capacity and VO2Max (2) to analyze the differences in the effect of Body Mass Index (BMI) on Time Exhaustion, Lung Vital Capacity and VO2Max (3) to analyze the interaction of the method exercise and Body Mass Index (BMI) on Exhaustion Time, Lung Vital Capacity and VO2Max. This research is quasi-experimental research with Pretest-Posttest Control Group design, using observation data collection-techniques, questionnaires. The data analysis technique used in this research was descriptive analysis, classical assumption test and hypothesis testing. The results showed that; (1) there is a difference in the effect of the Exercise Method on Time Exhaustion, Lung Vital Capacity and VO2Max with F count > F table and a significance value of 0.000 < 0.05, (2) there is a difference in the effect of Body Mass Index (BMI) on Time Exhaustion, Vital Capacity Lung and VO2Max, with F count > F table and significance value 0.000 < 0.05 (3) analyzed the interaction of Exercise Method and Body Mass Index (BMI) on Time Exhaustion, Lung Vital Capacity and VO2Max, with Q count > Q table.